Strategies to fight COVID-19: Beyond the difference between SARS-CoV-2 and Influenza virus - Huihui Lin; Hequan Li (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2022)
Background: Since the outbreak of COVID-19 emerged in Wuhan, China, in December 2019, the epidemic has spread worldwide and posed a great threat to society. Despite great achievements in COVID-19 research, few studies have focused on the similarities and differences between SARS-CoV-2 and influenza viruses.  Results: Through a review of the literature on SARS-CoV-2 and influenza viruses, we found that influenza occurs every year, and influenza pandemics occur irregularly. The uncomplicated human influenza viruses primarily affect the larger airways and rarely the alveoli. However, SARS-CoV-2 mainly involves the deep airways and lungs and can cause DAD, leading to severe hypoxemia. In general, SARS-CoV-2 is no less infectious than the influenza virus. However, its destructive power to the lungs is no less than the avian influenza virus. There is currently no clinical vaccine and specific inhibitor against SARS-CoV-2. Conclusions: SASR-CoV-2 damages lung function more severely than the influenza virus, with higher morbidity, mortality, and severe disease rates. Controlling the source of infection, cutting off the route of transmission, and protecting susceptible populations are critical to the fight against SARS-CoV-2.